Reduction of cybersickness in head mounted displays use: A systematic review and taxonomy of current strategies - Ang, Samuel; Quarles, John (Frontiers in Virtual Reality, 2023)
This literature review examines the existing research into cybersickness reduction with regards to head mounted display use. Cybersickness refers to a collection of negative symptoms sometimes experienced while immersed in a virtual environment, such as nausea, dizziness, or eye strain. These symptoms can prevent individuals from utilizing virtual reality (VR) technologies, so discovering new methods of reducing them is critical. Our objective in this literature review is to provide a better picture of what cybersickness reduction techniques exist, the quantity of research demonstrating their effectiveness, and the virtual scenes testing has taken place in. This will help to direct researches towards promising avenues, and illuminate gaps in the literature. Following the PRISMA statement, we obtained a batch of 1055 papers through the use of software aids. We selected 89 papers that examine potential cybersickness reduction approaches. Our acceptance criteria required that papers examined malleable conditions that could be conceivably modified for everyday use, examined techniques in conjunction with head mounted displays, and compared cybersickness levels between two or more user conditions. These papers were sorted into categories based on their general approach to combating cybersickness, and labeled based on the presence of statistically significant results, the use of virtual vehicles, the level of visual realism, and the virtual scene contents used in evaluation of their effectiveness. In doing this we have created a snapshot of the literature to date so that researchers may better understand what approaches are being researched, and the types of virtual experiences used in their evaluation.